Primary Dural Repair Using Titanium Microclips Following Lateral Skull Base Surgery - Milton, Camille K.; Bien, Alexander G.; Krempl, Greg A.; Sanclement, Jose A.; Mhawej, Rachad; Glenn, Chad A. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Standard techniques for primary dural repair following lateral skull base surgery are both technically challenging and time consuming without the potential for primary dural repair. Inadequate closure may result in postoperative cerebrospinal fluid (CSF) leak infectious sequalae. Traditional methods of dural repair rely on secondary obliteration of the CSF fistula. We hypothesized that the use of nonpenetrating titanium microclips may serve as a useful adjunct in primary dural repair or the establishment of an immobile repair layer following lateral skull base surgery.Methods Here, we report a novel technique for primary dural repair using nonpenetrating titanium microclips as an adjunct to standard techniques in a series of six patients with lateral skull base pathologies.Results A total of six consecutive lateral skull base tumor patients with titanium microclip dural reconstruction were included in our case series. Lateral skull base pathologies represented in this group included two jugular foramen schwannomas, one vestibular schwannoma, one petroclival meningioma, one glomus jugulare paraganglioma, and one jugular foramen chordoid meningioma.Conclusion To our knowledge, this is the first report on the use of microclips in repairing dural defects following lateral skull base surgery. Surgical outcomes for this small case series suggest that dural repair of the later skull base with nonpenetrating titanium microclips is a useful adjunct in dural repair following lateral skull base surgery.
Keywords: lateral skull base; dural closure; titanium microclip; tumor